« This is Hell – Hell - Hell ! » : les éléments dans The Nether World de George Gissing - Fabienne Gaspari (Cahiers Victoriens et Edouardiens)
In The Nether World, published in 1889, Gissing portrays the squalid life of the working class in London through a very pessimistic vision of British society. The urban setting, which is used as a backdrop, also plays a crucial role in the creation of a universe akin to hell. The evocations of the landscape and of nature, which are rare but extremely efficient, therefore seem to serve the unfolding of a perfectly orchestrated narrative. Such evocations generate clusters of images which are first meant to convey some grim picture of reality but which also lead to a poetic and fleeting representation of the elements, a reverie on the « dung-heap » (a metaphor defining the naturalist novel) and on the flowers which grow from it.